Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Water and Ethanol Extractsof Eleutherine palmifolia (L.) Merr. Against Staphylococcus aureus and Psedomonas aureginosa - Rusli, Rusli; Nurung, Ayyub Harly; Erwing, Erwing (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Dayak onion bulbs (Eleutherine palmifolia (L.) Merr.) are indigenous herbal plants found in Indonesia, rich in phytochemical compounds such as alkaloids, glycosides, flavonoids, phenolics, steroids, and tannins. This study investigates the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of water and ethanol extracts of Dayak onion bulbs against the bacteria Staphylococcus aureus and Pseudomonas aeruginosa. The water extract of Dayak onion bulbs was obtained by boiling using water, while the ethanol extract was obtained by maceration using 96% ethanol solvent. MIC and KBM were determined using the agar diffusion method. The results showed that water extract exhibited an MIC of 0.4% and MBC of 1.6% against both Staphylococcus aureus and Pseudomonas aeruginosa. Meanwhile, the ethanol extract demonstrated an MIC of 0.4% against Staphylococcus aureus and Pseudomonas aeruginosa bacteria with an MBC of 0.8% against Staphylococcus aureus bacteria and 1.6% against Pseudomonas aeruginosa bacteria. These findings suggest the potential of Dayak onion bulb extracts as antimicrobial agents against these pathogenic bacteria.